Feminism, domesticity and popular culture - Gillis, Stacy, 1972-; Hollows, Joanne (Routledge advances in sociology, 2009)
"This collection intervenes into the debates surrounding feminism's contentious relationship with domesticity in popular culture. The contributors touch on topics ranging from reality television shows like How Clean is Your House? to the figure of the maid in contemporary American cinema"--EBL